RAGAM BAHASA KOMUNITI PAKISTAN: SUATU ANALISIS LINGUISTIK - Nazir, Faridah (Journal of Techno-Social, 2013)
Language behaviour exists due to time factor and jobs for functional behaviour, location factor for the behavioural area and social factor in the community or society for social behaviour. Pakistan community is one of the minority communities in Malaysia besides Portuguese, Eurasian, Arabic and others. In general, Pakistan community in Malaysia is able to understand and speak four types of languages including Malay language, English, Punjabi and Urdu/Hindu language. This community is also capable in speaking and understanding particular dialects at the place where they are staying. The diversity of the acquisition of this community language bring about them to tend to use one specific language behaviour that was labelled by the researcher as social behaviour and areas that have the characteristicsof code mixing, code switching, reduction and dialects. This study gives focus on the language behaviour that was spoken by the Pakistan community in Rahang Kechil, Seremban, Negeri Sembilan was included through participation observation method, note taking method and spontaneous recording.